Developing a cognitive conservation model for the management of Malaysian birders' behavior toward birds - Jafarpour, Marjan; Ramkissoon, Haywantee (Frontiers in Sustainable Tourism, 2025)
IntroductionBirdwatching as a subcategory of ecotourism can create recreational disturbance. This research aims to assess two main goals: firstly, the effects of the frequency of participation (FOP) of Malaysian birders as moderators on the constructs of a Predictive Bird Conservation Model (PBCM). Secondly, the Importance–Performance Matrix Analyses (IPMA) of the PBCM, the extension builds on the partial least squares (PLS) estimates of the path model relationships.MethodsData was collected from 421 Malaysian birdwatchers using a field survey. We extend the theory of planned behavior (TPB) and cognitive hierarchy model (CHM), which was integrated into PBCM. The model was tested using the PLS approach.ResultsThe work explored the moderating role of FOP in all defined relationships in PBCM. Six hypotheses are proposed and tested.DiscussionThis research reflects the importance of FOP in moderating the relationship between value orientation and intention toward disturbance behavior among Malaysian birdwatchers and further shows the moderator role of FOP between Attitude and intention. FOP does not moderate other defined relationships in the PBCM. The study also enriches the birdwatching literature for decision-making sustainably. The findings provide useful managerial insights for policymakers and practitioners regarding bird-watching behavior.